Remittances from Saudi Arabia: A Community Phenomenon (The Pakistan Development Review, 2012)
Remittances are increasingly becoming an essential source of foreign exchange in developing countries, in some cases, even more than official development assistance. Recent estimates from the World Bank indicate that global remittances are expected to exceed $590 billion, with almost 75 percent of these remittances flowing to the developing countries. Pakistan became the fifth largest remittance-recipient nation in the developing world in 2011,1 registering a strong growth of 25.8 percent, relative to a 10.1 percent growth in remittances to South Asia. According to an IMF research paper, workers’ remittances contribute almost 4 percent to the country’s GDP, and are equivalent to almost 22 percent of annual exports of goods and services.2 Remittances to Pakistan have shown a strong rising trend; from being less than $2 billion dollars in 1997 to reaching almost $10 billion in 2010. In fact, the total remittances sent home by overseas Pakistani workers have more than quadrupled in the last eight years to more than $13.186 billion,3 the highest-ever amount received in a year by the country in the last fiscal year, which ended in June 2012. Interestingly, the almost 1.5 million Pakistani expatriates residing in Saudi Arabia send more remittances to Pakistan than from expatriates working and residing in other countries